2019
DOI: 10.1038/s41388-019-1078-x
|View full text |Cite
|
Sign up to set email alerts
|

The reciprocal interaction between tumor cells and activated fibroblasts mediated by TNF-α/IL-33/ST2L signaling promotes gastric cancer metastasis

Abstract: Gastric cancer (GC) is characterized by extensive local invasion, distant metastasis and poor prognosis. In most cases, GC progression is associated with aberrant expression of cytokines or activation of signaling cascades mediated by tumor-stroma interactions. However, the mechanisms by which these interactions contribute to GC progression are poorly understood. In this study, we find that IL-33 and its receptor ST2L are upregulated in the human GC and served as prognostic markers for poor survival of GC pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
73
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(75 citation statements)
references
References 55 publications
2
73
0
Order By: Relevance
“…CAFs release a significant amount of galectin-1, which promotes EMT and gastric cancer progression by binding to β1 integrin [260]. EMT is also promoted by CAFs-derived IL-33 through the activation of the ERK1/2-SP1-ZEB2 pathway [261].…”
Section: Cancer-associated Fibroblastsmentioning
confidence: 99%
“…CAFs release a significant amount of galectin-1, which promotes EMT and gastric cancer progression by binding to β1 integrin [260]. EMT is also promoted by CAFs-derived IL-33 through the activation of the ERK1/2-SP1-ZEB2 pathway [261].…”
Section: Cancer-associated Fibroblastsmentioning
confidence: 99%
“…On the other hand, CAFs can enhance the metastatic potential of cancer cells by the induction of EMT, through the paracrine secretion of transforming growth factor-β (TGF-β),which promotes cancer cell invasion [ 88 , 89 ] and the differentiation of CAFs in an autocrine fashion [ 90 ], CXCL12 [ 91 ], interleukin 6 (IL-6) [ 92 , 93 ], or matrix metalloproteinases (MMPs) [ 94 ]. CAF-induced EMT is also shown in experimental settings using conditioned media and co-cultures [ 95 , 96 , 97 , 98 ]. In addition, TGF-β together with some chemokines and cytokines such as IL-6 and CXCL9 promote cancer progression by suppressing the antitumor immune response leading to the disruption of T cell function and cancer cell immune evasion [ 99 , 100 ].…”
Section: Cancer-associated Fibroblasts (Cafs)mentioning
confidence: 99%
“…The cell-to-cell interaction between CAFs and the tumor cells and other surrounding cells including cancer-associated macrophages (CAMs) is essential [112]. In a recent study, CAFs-derived interleukin-33 (IL-33) has been found to mediate the activation of the ERK1/2-SP1-ZEB2 pathway through its receptor ST2L [113]. The secretion of IL-33 by CAFs can be stimulated by TNF-α released by the surrounding GC cells.…”
Section: Cafs and Signaling Pathwaysmentioning
confidence: 99%